Endoscopic Resection of Tailgut Cyst - Oleksandr Kiosov; Vladyslav Tkachov; Sergii Gulevskyi (Case Reports in Gastrointestinal Medicine)
Tailgut cyst or retrorectal cystic hamartoma is a rare congenital lesion, thought to arise from a portion of the embryological hindgut, usually benign, with no or unspecific symptoms, mainly diagnosed in middle-aged women. Complete surgical resection of the cyst is recommended to avoid complications and confirm the diagnosis. In this report, we present our experience in the successful endoscopic management of a tailgut cyst, outlining the endoscopic resection technique and discussing under what conditions this approach may be applicable.